The effects of television advertising on materialism and life satisfaction: A study with Algerian university students - Belhaj, Tarek (Milev Journal of Research and Studies, 2017)
Previous research in the unintended effects of television advertising has been conducted largely in Western countries with little research being conducted in other setting. The results suggest that The development of people’s satisfaction with life seems to contradict the growth in materialistic consumption promoted by advertising messages. This study examined the effects of television advertising on materialistic tendencies and life satisfaction in a non-Western setting. In a first step, a conceptual model based on existing hypotheses was developed, and in a second step, this model was tested using a sample of 131 Algerian students. Using regression analysis and structural equation modeling, the findings show that advertising exposure is positively related to materialism and negatively related to life satisfaction. The results suggest that the effects of advertising on both materialism and life satisfaction could be moderated by the extent to which advertising is perceived to be materialistic. Materialism, in turn, contributes significantly to dissatisfaction with life.